A Simplified Management of Transverse Testicular Ectopia in Patients with Persistent Mullerian Duct Syndrome - Silveri, Massimiliano; Zaccara, Antonio; Cappa, Marco (Urology Journal, 2020)
Persistent müllerian duct syndrome (PMDS) in the majority of cases is discovered during surgery for inguinal hernia or cryptorchidism. A transverse testicular ectopia (TTE) with cryptorchidism may be very rarely associated to PMDS. Assuming that müllerian remnants have a very low malignant degeneration potential if compared to the malignancy risk of an undescended and not relocated testis, we describe a simplified surgical technique of orchiopexy that avoids an extensive anatomical dissection, in this way minimizing the risk of losing the deferential blood supply to the testis.